2001
DOI: 10.1078/0944-5013-00074
|View full text |Cite
|
Sign up to set email alerts
|

Epiphytic microflora of poplar clones susceptible and resistant to infection by Dothichiza populea

Abstract: One-year-old poplar shoots (nodes, internodes and lenticels) of clones susceptible to infection by the pathogenic fungus Dothichiza populea, viz. Populus nigra Italica and P. Robusta, resistant ones, viz. P. Grandis and P. Hybrida 275, as well as a hybrid of a susceptible and a resistant clone, viz. P. maximowiczii x P. nigra (P. Kórnik 42), were used. The plate method was employed to determine: 1. the abundance of the epiphytic microflora on a mineral medium with glucose; 2. the quantitative composition of ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The global population of phyllosphere microbes is estimated to be ∼10 26 cells ( Lindow and Brandl, 2003 ). Culture-based isolation studies have shown that phyllosphere microbial communities include many important taxa, including plant pathogens, ice nucleation-active bacteria ( Hirano and Upper, 2000 ), decomposers ( Hicks and Silvester, 1985 ), phytohormone producers ( Fett et al, 1987 ), nitrogen fixers ( Furnkranz et al, 2008 ), and antagonists of plant pathogens ( Weyman-Kaczmarkowa and Pedziwilk, 2001 ). Phototrophic microbes also colonize some plant leaves, including rhodopsin-based ones, absorbing different fractions of the light spectrum ( Atamna-Ismaeel et al, 2012b ).…”
Section: Introductionmentioning
confidence: 99%
“…The global population of phyllosphere microbes is estimated to be ∼10 26 cells ( Lindow and Brandl, 2003 ). Culture-based isolation studies have shown that phyllosphere microbial communities include many important taxa, including plant pathogens, ice nucleation-active bacteria ( Hirano and Upper, 2000 ), decomposers ( Hicks and Silvester, 1985 ), phytohormone producers ( Fett et al, 1987 ), nitrogen fixers ( Furnkranz et al, 2008 ), and antagonists of plant pathogens ( Weyman-Kaczmarkowa and Pedziwilk, 2001 ). Phototrophic microbes also colonize some plant leaves, including rhodopsin-based ones, absorbing different fractions of the light spectrum ( Atamna-Ismaeel et al, 2012b ).…”
Section: Introductionmentioning
confidence: 99%
“…Epiphytic bacteria are the main inhabitants of the phyllosphere, and are estimated to have a density of 10 6 -10 7 CFU cm −2 on a typical leaf (20). Culture-based studies have shown that such bacteria may include plant pathogens, ice nucleation-active bacteria, decomposers, phytohormoneproducers, nitrogen fixers, and antagonists of plant pathogens (8,10,11,14,25,35). Traditionally, bacterial communities in the phyllosphere were thought to be highly variable in both quantity and quality (9, 13, 33).…”
mentioning
confidence: 99%
“…Epiphytic bacteria are the main inhabitants of the phyllosphere, and are estimated to have a density of 10 6 to 10 7 CFU cm −2 on a typical leaf 14) . Traditional isolation studies have shown that such bacteria include plant pathogens, ice nucleation-active bacteria, decomposers, phytohormone producers, nitrogen fixers, and antagonists of plant pathogens 3,4,6,8,17,26) . However, recent studies have revealed that many microorganisms in this environment are non-culturable.…”
mentioning
confidence: 99%